Composite sheet

By dispersing and fixing the metal organic structure in the core sheath fiber sheet base material of the non-woven fabric, the problem of poor MOF loading inside the non-woven fabric is solved, and the gas adsorption performance and stability are improved.

CN119731387APending Publication Date: 2025-03-28KAO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480003673.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-12
Filing Date
2024-06-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively carry metal organic structures (MOFs) inside the non-woven fabric, resulting in poor gas adsorption performance of MOFs and prone to falling off.

Method used

By dispersing the metal organic structure in the sheet base material composed of core sheath fibers, the MOF is melted and fixed by using the resin in the sheath portion of the core sheath fibers to ensure that the surface exposure rate of the MOF reaches more than 50%.

Benefits of technology

It realizes high-efficiency loading of MOF inside the non-woven fabric, improves gas adsorption performance, and prevents MOF from falling off, ensuring the stability and performance of the composite sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731387A_ABST
    Figure CN119731387A_ABST
Patent Text Reader

Abstract

Provided is a composite sheet in which a metal-organic structure is supported on a sheet base material comprising fibers, the composite sheet having high gas adsorption performance, and the metal-organic structure being unlikely to fall off during use. In the composite sheet, a metal-organic structure is dispersed in a sheet base material comprising fibers. The fibers include core-sheath fibers having a core-sheath structure composed of a core portion and a sheath portion. The metal-organic structure is supported by melting and fixing the resin of the sheath portion of the core-sheath fiber. The surface exposure rate of the metal-organic structure supported by the sheath portion of the core-sheath fiber is 50% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite sheet in which a metal-organic structure is supported on a sheet substrate. Background Art

[0002] Metal organic framework (MOF) has uniform pore size, high specific surface area, high separation performance, etc., and therefore has attracted much attention as a high-performance gas adsorption material. On the other hand, MOF is known to be a micron-sized powder, so it is difficult to process it as a single substance. In contrast, there is a known technology for processing a large amount of MOF at one time by supporting MOF on a substrate such as a non-woven fabric (for example, refer to Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2021-191913

[0006] Patent Document 2: U.S. Patent Application Publication No. 2021 / 0189620

[0007] Patent Document 3: Chinese Patent Application Publication No. 112002938 Summary of the invention

[0008] Technical problem to be solved by the invention

[0009] In order to improve the gas adsorption performance, a large amount of MOF needs to be carried in the nonwoven fabric. For this reason, it is more advantageous to carry MOF not only on the surface of the nonwoven fabric but also inside. However, by common methods such as a method of dispersing MOF particles on the nonwoven fabric and a method of impregnating the nonwoven fabric with a MOF dispersion, each MOF particle does not enter the inside of the nonwoven fabric and tends to stay on the surface.

[0010] The fibers that make up the nonwoven fabric do not have the function of fixing MOF on their surface. Therefore, even if you want to load more MOF on the nonwoven fabric, the MOF that is not sufficiently fixed will fall off the nonwoven fabric, making it difficult to fully exert gas adsorption performance during use.

[0011] It is known that there is a technology that uses an adhesive to fix MOF on the surface of fibers constituting nonwoven fabrics. However, in the case of a technology that mainly relies on an adhesive to fix MOF, the pores of MOF are blocked by the adhesive attached to the surface of MOF, thereby easily impairing the original gas adsorption performance of MOF.

[0012] The technical problem of the present invention is to provide a composite sheet in which a metal organic structure is supported in a sheet substrate composed of fibers, the gas adsorption performance is high, and the metal organic structure is not likely to fall off during use.

[0013] Technical solutions for solving technical problems

[0014] In the composite sheet according to one embodiment of the present invention, the metal organic structure is dispersed in the sheet base material composed of fibers.

[0015] In one embodiment, the fiber includes a core-sheath fiber having a core-sheath structure consisting of a core portion and a sheath portion.

[0016] In one embodiment, the metal organic structure is supported by melting and fixing the resin of the sheath portion of the core-sheath fiber.

[0017] In one embodiment, the surface exposure rate of the metal organic structure carried by the sheath portion of the core-sheath fiber is 50% or more.

[0018] Effects of the Invention

[0019] According to the present invention, it is possible to provide a composite sheet in which a metal-organic structure is supported on a sheet base material composed of fibers, the composite sheet has high gas adsorption performance, and the metal-organic structure is unlikely to fall off during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a flowchart showing a method for producing a composite sheet according to one embodiment of the present invention. DETAILED DESCRIPTION

[0021] [Basic structure of composite sheet]

[0022] A composite sheet according to one embodiment of the present invention includes a sheet substrate and a metal organic structure (MOF: Metal Organic Framework).

[0023] The sheet base material of the composite sheet of the present embodiment is a base material formed into a sheet shape using fibers, and is typically a nonwoven fabric, but may also be a woven fabric, a knitted fabric, a mesh fabric, or the like.

[0024] The MOF of the composite sheet of this embodiment is typically a fine powder composed of metal ions and organic ligands, which is dispersed in the sheet substrate and carried on the surface of the fibers constituting the sheet substrate. In addition, such a structure is sometimes referred to as a porous coordination polymer (PCP), but in this specification, it is uniformly referred to as a metal organic structure (MOF).

[0025] In the composite sheet of the present embodiment, the fibers constituting the sheet base material include core-sheath fibers. The core-sheath fibers are composite fibers in which the resin constituting the core portion and the resin constituting the sheath portion that covers the core portion and constitutes the surface of the fiber are different from each other.

[0026] In the core-sheath fiber used in the present embodiment, the melting point of the core part is preferably higher than the melting point of the sheath part, and the difference between the melting point of the core part and the melting point of the sheath part is more preferably 10°C or more and 200°C or less, more preferably 60°C or more, and more preferably 100°C or more. By adopting such a structure, in the manufacturing process of the composite sheet of the present embodiment, the core part with a high melting point can maintain the form as a fiber. That is, in step S05 described later, the melting of the sheath part can occur more reliably, and the melting of the core part caused by overshoot during heating can be easily avoided. In addition, the MOF can be supported by melting the resin of the sheath part with a low melting point and fixing it to the MOF.

[0027] In the core-sheath fiber used in the present embodiment, the melting point of the core portion is preferably 160° C. or higher and 280° C. or lower, more preferably 200° C. or higher, and further preferably 240° C. or higher. In the composite sheet of the present embodiment, by making the melting point of the core portion of the core-sheath fiber contained in the fiber constituting the sheet base material high in this way, gas recovery from high-temperature exhaust gas generated in factories and the like can be performed, and the scope of use can be further expanded.

[0028] In the core-sheath fiber used in the present embodiment, the melting point of the sheath portion is preferably 70° C. or higher and lower than 160° C., more preferably 80° C. or higher, and even more preferably 100° C. or higher. By increasing the melting point of the sheath portion of the core-sheath fiber in this way, the drying temperature in step S04 described later can be increased, and drying can be achieved in a shorter time.

[0029] In the present embodiment, the fibers constituting the sheet base material preferably include, for example, core-sheath fibers in which the core portion is composed of polyethylene terephthalate and the sheath portion is composed of polyethylene.

[0030] In addition, in the core-sheath fiber of the present embodiment, at least one of the core part and the sheath part may contain multiple resin components. In this case, the melting point of the core part represents the melting point of any resin component contained in the core part, and the melting point of the sheath part represents the melting point of any resin component contained in the sheath part.

[0031] Each particle of MOF used in the composite sheet of the present embodiment is typically porous and has a large number of pores having a uniform pore diameter, and functions as a gas adsorbent by adsorbing and retaining gas molecules in each pore.

[0032] The composite sheet of the present embodiment is a gas adsorption sheet having a structure in which a large amount of MOF is collectively supported on a sheet substrate in a state where the gas adsorption performance can be effectively exhibited, and the MOF supported on the sheet substrate as a whole can adsorb a large amount of gas.

[0033] In the composite sheet of the present embodiment, typically, a MOF layer is formed on the surface of the fiber.

[0034] The MOF layer refers to a state in which the aggregate of MOF particles forms a layer as a whole. Specifically, the MOF layer includes one or more of the following states: a state in which a plurality of micropowdered or granular MOFs are stacked and laminated on the surface of a fiber; a state in which the micropowdered or granular MOFs are generated and grown on the surface of a fiber and the surface of the fiber is coated with the MOFs; a state in which adjacent MOF particles are integrated with each other during generation and growth and the surface of the fiber is coated with an integrated film.

[0035] The MOF layer is preferably in a state where the surface of the fiber is covered in the form of an integrated film. Thus, the MOF is not easily detached from the fiber. Furthermore, when the sheath portion of the core-sheath fiber melts, the resin constituting the melted sheath portion can be prevented from adhering to the MOF fixed to other core-sheath fibers.

[0036] In the composite sheet of the present embodiment, the particle diameter of MOF may be larger or smaller than the fiber diameter of the sheet base material.

[0037] Among the MOFs that can be used in the composite sheet of this embodiment, there are MOFs with various pore sizes due to the combination of metal ions and organic ligands. Therefore, in the composite sheet of this embodiment, the pore size of the MOF supported on the sheet substrate can be determined according to the molecular size of the gas to be adsorbed. Thus, in the composite sheet of this embodiment, a specific gas can be selectively adsorbed according to the MOF supported on the sheet substrate.

[0038] In the composite sheet of this embodiment, for example, by using a MOF that can selectively adsorb carbon dioxide, carbon dioxide known as a greenhouse gas can be recovered and used as a chemical raw material, etc. The composite sheet of this embodiment uses a MOF that can selectively adsorb hydrocarbons (methane, ethane, propane, etc.), hydrogen, hydrogen sulfide, nitrogen and / or oxygen in addition to carbon dioxide, and can be configured as a gas adsorption sheet corresponding to these gases.

[0039] In the composite sheet of the present embodiment, the effect of the present invention can be obtained when any type of various MOF is used. That is, MOF is synthesized by self-assembly based on the coordination bond of metal ions and organic ligands. Its reaction mechanism is independent of the types of metal ions and organic ligands and is the same. Regarding MOF, since the combination of metal ions and organic ligands is infinite in principle, the combination of MOF has infinite possibilities. At this time, according to the type and adsorption characteristics of the adsorbed gas, it is possible to consider the type of metal ions, the shape, length, substituents of the ligands, etc. to select and synthesize MOF, thereby being able to arbitrarily adjust the shape of the resulting nano space. As can be seen from the above, the present invention can obtain the same effect for any MOF.

[0040] [Basic structure of the method for producing a composite sheet]

[0041] (Brief description)

[0042] according to Figure 1 The flowchart shown in FIG. 1 illustrates the basic structure of the method for producing a composite sheet according to the present embodiment. Figure 1 The composite sheet manufacturing method shown includes step S01 (raw material solution preparation), step S02 (first raw material solution impregnation), step S03 (second raw material solution impregnation), step S04 (drying) and step S05 (heat treatment). Steps S01 to S05 of this embodiment are described below.

[0043] (Step S01: Raw material solution preparation)

[0044] In step S01, a first raw material solution and a second raw material solution are prepared as raw material solutions of MOF. The first raw material solution and the second raw material solution are solutions containing either metal ions and organic ligands as raw materials of MOF. They are mixed with each other, whereby the metal ions and the organic ligands react to generate MOF.

[0045] In this embodiment, the first raw material solution contains metal ions as solutes, and the second raw material solution contains organic ligands as solutes.

[0046] In the present embodiment, it is preferred that the solvent of the first raw material solution contains water.

[0047] In the present embodiment, it is preferred that the solvent of the second raw material solution contains ethanol.

[0048] As an example of step S01, when the MOF is ELM-11 (ELM=Elastic Layer-structured Metalorganic framework), an aqueous solution of Cu(BF4)2 is prepared as a first raw material solution, and an ethanol solution of 4,4'-bipyridine (bpy) is prepared as a second raw material solution.

[0049] (Step S02: Immersion in the First Raw Material Solution)

[0050] In step S02 , the sheet base material is impregnated with the first raw material solution prepared in step S01 .

[0051] The method of impregnating the sheet substrate with the first raw material solution in step S02 is not limited to a specific method. For example, a method of impregnating the sheet substrate with a sufficient amount of the first raw material solution using one or more selected from dropper addition, spraying, spray coating, die coating, curtain coating, and dip coating can be adopted. Among these, from the viewpoint of preventing the occurrence of contamination in the first raw material solution, one or more selected from dropper addition, spraying, spray coating, die coating, and curtain coating are preferably used.

[0052] In step S02 , from the viewpoint of allowing the first raw material solution to penetrate into the center portion of the sheet base, the time for immersing the sheet base with the first raw material solution is preferably 0.1 minute or longer.

[0053] Furthermore, the time for impregnating the sheet substrate with the first raw material solution is preferably 30 minutes or less from the viewpoint of ensuring productivity.

[0054] In step S02 , it is preferred that the metal ions contained in the first raw material solution be uniformly diffused throughout the entire sheet substrate together with the solvent.

[0055] (Step S03: Impregnation with the Second Raw Material Solution)

[0056] In step S03 , the sheet base material impregnated with the first raw material solution in step S02 is impregnated with the second raw material solution prepared in step S01 while the first raw material solution is not dried.

[0057] Thus, even when the solute of the first raw material solution is difficult to dissolve in the solute of the second raw material solution, the reaction between the solute of the first raw material solution and the solute of the second raw material solution can be smoothly performed.

[0058] Furthermore, even when the solute of the first raw material solution is dissolved in the solute of the second raw material solution, the reaction between the solute of the first raw material solution and the solute of the second raw material solution can be uniformly performed.

[0059] The state in which the first raw material solution in the sheet substrate is not dried refers to a state in which the solvent of the first raw material solution remains in the sheet substrate, more specifically, a state in which 50% or more of the solvent of the first raw material solution remains in the sheet substrate compared to before impregnation. Among them, from the viewpoint of preventing the occurrence of contamination in the first raw material solution, it is preferred to use one or more selected from the group consisting of dropper dripping, spraying, spray coating, die coating and flow coating. The amount of the second raw material solution is preferably set to an amount corresponding to the amount of the first raw material solution impregnated in step S02.

[0060] In step S03 , the time for immersing the sheet substrate in the second raw material solution is preferably 0.1 minute or longer from the viewpoint of allowing the second raw material solution to penetrate into the center portion of the sheet substrate.

[0061] Furthermore, the time for impregnating the sheet substrate with the second raw material solution is preferably 30 minutes or less from the viewpoint of ensuring productivity.

[0062] The method of impregnating the sheet substrate with the second raw material solution in step S03 is not limited to a specific method. For example, a method of dripping the second raw material solution onto the sheet substrate using one or more selected from the group consisting of dripping with a dropper, spraying, spray coating, die coating, flow coating, and dip coating can be adopted. The amount of the second raw material solution is preferably set to an amount corresponding to the amount of the first raw material solution impregnated in step S02.

[0063] In step S03 , the organic ligand contained in the second raw material solution is preferably uniformly diffused throughout the entire sheet substrate together with the solvent.

[0064] In step S02 , the organic ligand reacts with the metal ions diffused into the sheet substrate to generate MOF.

[0065] As an example of step S03, when the MOF is ELM-11, Cu(BF4)2 contained in the first raw material solution and bpy contained in the second raw material solution react as follows, thereby generating ELM-11.

[0066] Cu(BF4)2+2bpy→Cu(bpy)2(BF4)2

[0067] In the manufacturing process of a conventional composite sheet, the pre-generated MOF is carried on the sheet substrate. Therefore, each particle of MOF cannot pass through the gaps between the fibers constituting the sheet substrate and enter the interior, and is likely to remain on the surface portion near the surface of the sheet substrate. That is, in the manufacturing process of a conventional composite sheet, MOF tends to be biased towards the surface portion of the sheet substrate. On the contrary, in a substrate structure in which MOF enters the interior of the sheet substrate, it will fall off quickly, and it is difficult to increase the amount of MOF carried.

[0068] In contrast, in the manufacturing process of the composite sheet of the present embodiment, typically, the raw materials before the generation of MOF, i.e., metal ions and organic ligands, are diffused in the sheet substrate at the molecular level. By subsequently generating MOF particles, a large amount of MOF can be carried not only on the surface of the sheet substrate, but also in the center in the thickness direction.

[0069] Here, the "central portion in the thickness direction" refers to the middle portion when the thickness direction is equally divided into three regions.

[0070] In the manufacturing process of the composite sheet of the present embodiment, the above advantages can also be obtained in the configuration of a thick sheet substrate, so by using a thick sheet substrate, more MOF can be carried. From this point of view, in the present embodiment, the thickness of the composite sheet is preferably 0.2 mm or more, more preferably 0.5 mm or more, and further preferably 1 mm or more.

[0071] The thickness of the composite sheet is practically 10 mm or less, preferably 5 mm or less.

[0072] Regarding the thickness of the composite sheet, the load was set to 3.7 gf / cm according to JIS K6402. 2 , set the pressing surface area of ​​the measuring head to 10cm 2 , find the average value of the values ​​measured at a total of 5 locations, namely, 4 corners and 1 central location when viewed from above.

[0073] In the above-mentioned conventional composite sheet manufacturing process, during the process of spreading or coating MOF on the sheet substrate, there are few MOF particles that go around the area on the opposite side of the fiber on the spreading or coating surface. Therefore, it is difficult to uniformly carry MOF over the entire circumference of the fiber surface.

[0074] In contrast, in the manufacturing process of the composite sheet of the present embodiment, metal ions and organic ligands can be diffused uniformly throughout the three-dimensional structure of the sheet substrate together with the solvent, so that MOF can be uniformly supported over the entire circumference of the surface of the fibers constituting the sheet substrate.

[0075] As a comparative structural example relative to the present embodiment, a manufacturing process using a method of drying a sheet substrate impregnated with a first raw material solution before step S03 is described. In the manufacturing process of the composite sheet of the comparative structural example, in the process of drying the sheet substrate before step S03, the solvent evaporates and is removed from the surface side of the sheet substrate. Therefore, the solvent in the central part of the thickness direction of the sheet substrate diffuses to the surface side together with the metal ions and solidifies. Thus, in the manufacturing process of the composite sheet of the comparative structural example, in the sheet substrate before impregnation with the second raw material solution, the solute of the first raw material solution is biased towards the surface part. Therefore, the amount of MOF that can be generated in the central part of the thickness direction of the sheet substrate decreases. In addition, in the manufacturing process of the composite sheet of the comparative structural example, in the sheet substrate before impregnation with the second raw material solution, the solute of the first raw material solution is generated in the form of a solid. Therefore, even if the second raw material solution is impregnated, the solute of the first raw material solution is difficult to dissolve in the solvent of the second raw material solution to generate metal ionization. As a result, the metal ions do not react with the organic ligands and are easily left as unreacted substances.

[0076] In the composite sheet manufacturing process of this embodiment, it is preferred that the sheet base impregnated with the first raw material solution is not dried in step S02, and the sheet base in the presence of the solvent of the first raw material solution is impregnated with the second raw material solution in step S03.

[0077] That is, in the composite sheet manufacturing process of this embodiment, the metal ions contained in the first raw material solution can be reacted with the organic ligands contained in the second raw material solution while being uniformly dispersed in the sheet substrate.

[0078] In addition, in the manufacturing process of the composite sheet of the present embodiment, the reaction is promoted by effectively combining the metal ions and organic ligands that exist without restraint in the solvent. Therefore, the metal ions and organic ligands are unlikely to remain as unreacted products.

[0079] Therefore, in the manufacturing process of the composite sheet of the present embodiment, more MOF can be supported on the sheet base material compared to the manufacturing process of the composite sheet of the comparative configuration example.

[0080] In the manufacturing process of the composite sheet of the present embodiment, it is believed that the reaction of metal ions and organic ligands is accompanied by non-uniform nucleation in the interface of the fiber constituting the sheet substrate. Intermolecular forces act between the MOF generated by non-uniform nucleation and the interface of the fiber. Therefore, the MOF generated in step S03 is directly supported on the interface of the fiber through the intermolecular force without other components. Therefore, in the manufacturing process of the composite sheet of the present embodiment, it is not necessary to use an adhesive as a bonding component in order to support MOF on the surface of the fiber.

[0081] In addition, in this specification, "MOF is directly supported on the surface of the fiber" means that MOF is fixed to the surface of the fiber without other components other than MOF and fiber material. Typically, as described above, it is fixed by intermolecular forces, fixed by hydrophobic interactions described later, or fixed by melting and fixing the resin on the surface of the fiber to MOF.

[0082] The fact that the resin on the surface of the fiber is melted and fixed to the MOF can be confirmed by observing the cross section of the fiber constituting the composite sheet using a scanning electron microscope (SEM). That is, when the resin in the sheath portion of the core-sheath fiber is melted and fixed to the MOF, the MOF becomes sunken into the sheath portion of the core-sheath fiber, and thus, at the boundary between the MOF and the core-sheath fiber, the contour of the core-sheath fiber, which is originally circular, is observed to be distorted.

[0083] Thus, in the case of the composite sheet of the present embodiment, it is not easy to cause the gas adsorption performance of MOF to decrease due to the adhesion of the adhesive, the flexibility to decrease due to the adhesive, and other performance reductions caused by the presence of the adhesive. Therefore, in the composite sheet of the present invention, it is preferred that MOF is directly supported on the surface of the fiber. Such an effect is mainly obtained by the generation of MOF achieved by the reaction of the metal ions and the organic ligands as described above, and is not limited to the structures illustrated in the embodiments described later, and structures other than these can also be effectively obtained.

[0084] In the composite sheet of the present embodiment, the distance between fibers defined as the size of the gap between the fibers constituting the sheet substrate is preferably 1 μm or more, more preferably 10 μm or more, further preferably 50 μm or more, and further preferably 100 μm or more. Thus, the structural flexibility of the MOF carried on the surface of the fiber can be ensured, and the falling of the MOF can be suppressed. That is, the high flexibility of the composite sheet can be easily obtained, and the MOF formation space can be ensured to increase the carrying rate.

[0085] In addition, the distance between fibers is preferably 1000 μm or less, more preferably 500 μm or less, further preferably 400 μm or less, and further preferably 300 μm or less. Thus, when the metal ions react with the organic ligands, homogeneous nucleation is suppressed and heterogeneous nucleation occurs more effectively. That is, the formation site of MOF can be controlled on the surface of the fiber.

[0086] The method for measuring the distance between fibers of the sheet substrate in the composite sheet of the present embodiment is described. First, an arbitrary surface of the composite sheet of the measurement object is observed by SEM to obtain an enlarged image of the surface. In the enlarged image, 50 voids formed by each fiber are selected, and the total area of ​​the voids is measured, divided by the number of voids 50, thereby calculating the average void area per void. From the average void area per void obtained here, the average fiber diameter when the void is converted into a circle is calculated by the following formula, and the average fiber diameter is used as the fiber distance.

[0087] Average inter-fiber diameter = 2×(average interstitial area / 3.14)^(1 / 2)

[0088] In the composite sheet of the present embodiment, the basis weight of the sheet base material is preferably 10 g / m 2 More preferably 20 g / m 2 More than, preferably 100g / m 2 Below, more preferably 80g / m 2 In addition, when the sheet substrates are stacked and used as one sheet substrate, the total gram weight of the sheet substrates is preferably more than 100 g / m 2 structure.

[0089] (Step S04: Drying)

[0090] In step S04, the sheet substrate on which the MOF is supported in step S03 is dried.

[0091] In addition, in step S04, during the drying process, the solvent evaporates from the surface side of the sheet substrate and is removed, and the solvent in the central part of the thickness direction of the sheet substrate diffuses to the surface side. However, the MOF that has been fixed to the surface of the fiber in the central part of the thickness direction of the sheet substrate does not move with the solvent and remains on the surface of the fiber. Therefore, in the manufacturing method of the composite sheet of this embodiment, the dispersed state of the MOF supported on the sheet substrate is maintained in step S04.

[0092] In the method for producing a composite sheet of the present invention, the total number of times a series of steps S02 to S04 are performed may be 1. That is, the steps may not be repeated.

[0093] On the other hand, by repeatedly performing steps S02 to S04, the amount of MOF supported on the sheet substrate can be increased. From this viewpoint, the total number of times steps S02 to S04 are performed is preferably 2 or more, more preferably 3 or more.

[0094] Furthermore, since there is a limit to the amount of MOF that can be supported on the sheet substrate, in the composite sheet manufacturing method of the present embodiment, the total number of steps S02 to S04 is preferably limited to 20 times or less from the viewpoint of manufacturing cost and the like.

[0095] (Step S05: Heat Treatment)

[0096] In step S05, the sheet substrate dried in step S04 is subjected to heat treatment. The heat treatment in step S05 is preferably performed at a temperature that is higher than the melting point of the sheath portion and lower than the melting point of the core portion. For example, the heat treatment in step S05 can be performed by maintaining at 140°C for 2 hours.

[0097] The MOF generated in step S03 is in a hydrated state and therefore has no gas adsorption function.

[0098] In step S05 , it is preferred that the solvent component remaining in the sheet base material is completely removed.

[0099] In step S05 , the gas adsorption function of MOF can be exhibited by dehydrating MOF, thereby obtaining the composite sheet of the present embodiment.

[0100] In step S05, by performing heat treatment in the above-mentioned temperature range, only the sheath portion with a low melting point in the core-sheath fiber contained in the fiber constituting the sheet substrate melts or softens. As a result, in the composite sheet after heat treatment, the MOF is carried on the surface of the core-sheath fiber by melt fixation. That is, in the composite sheet of this embodiment, the sheath portion of the core-sheath fiber can be fixed to the MOF without adding an adhesive as an adhesive component.

[0101] On the other hand, in step S05, the core portion having a high melting point is less likely to melt and soften during the heat treatment process. Therefore, in the composite sheet after the heat treatment, the fibers constituting the sheet base material also maintain the form of fibers in the core portion.

[0102] In the sheet substrate used in the present embodiment, the more core-sheath fibers there are, the more effectively MOF can be prevented from falling off. From this viewpoint, in the sheet substrate used in the present embodiment, the content of the core-sheath fibers is preferably 3% by mass or more, more preferably 10% by mass or more, and further preferably 30% by mass or more.

[0103] The content of the core-sheath fibers in the sheet base material is less than 100% by mass, preferably 90% by mass or less, and more preferably 80% by mass or less.

[0104] The content of the core-sheath fibers in the composite sheet is preferably 1% by mass or more, more preferably 2% by mass or more.

[0105] The content of the core-sheath fibers in the composite sheet is preferably 20% by mass or less, more preferably 18% by mass or less.

[0106] In the manufacturing process of a conventional composite sheet in which the MOF generated in advance as described above is carried on a sheet substrate, when heat treatment is performed, for one MOF particle, the melted sheath portion of the adjacent multiple core-sheath fibers is easy to adhere. In contrast, in the manufacturing process of the composite sheet of the present embodiment, since the sheath portion constituting the surface of the core-sheath fiber is covered with MOF at the stage of step S03, the melted sheath portion of the core-sheath fiber is not easy to adhere to the MOF carried on other core-sheath fibers in step S05. As a result, in the composite sheet of the present embodiment, the MOF carried on the sheet substrate can more effectively exert its original gas adsorption performance.

[0107] In addition, in the composite sheet of this embodiment, compared with a composite sheet obtained by a conventional composite sheet manufacturing process, it is easier to obtain high MOF loading, and MOF is less likely to fall off from the core-sheath fibers, which also contributes to effective gas adsorption performance.

[0108] Hereinafter, the relationship between the drying temperature in step S04 and the heat treatment temperature in step S05 in the method for producing a composite sheet according to the present embodiment and the structure of the core-sheath fiber will be summarized.

[0109] In the core-sheath fiber of the present embodiment, it is preferred that the melting point of the core portion is higher than the heat treatment temperature in step S05.

[0110] In the core-sheath fiber, it is preferred that the melting point of the sheath portion is higher than the drying temperature in step S04 and lower than the heat treatment temperature in step S05.

[0111] In the manufacturing method of the composite sheet of the present embodiment, by making the melting point of the sheath portion of the core-sheath fiber higher than the drying temperature in step S04, it is possible to prevent the sheath portion from melting in step S04 and introducing the reactants into the fiber. Therefore, the MOF generation reaction can be reliably performed and the reactivity of the MOF generation reaction can be improved.

[0112] In addition, by making the melting point of the sheath portion of the core-sheath fiber lower than the heat treatment temperature in step S05, MOF can be more reliably solidified on the surface of the fiber. In addition, by making the melting point of the core portion of the core-sheath fiber higher than the heat treatment temperature in step S05, the fiber shape can be maintained by the unmelted core portion in step S05. Therefore, the gap between the fibers of the sheet substrate can be maintained, and the reactivity of the MOF generation reaction can be improved.

[0113] [Other structural examples of the method for producing a composite sheet]

[0114] The manufacturing method of the composite sheet of the present embodiment is not limited to the above basic structure. For example, in the manufacturing method of the composite sheet of the present embodiment, preferably in step S01, one of the metal ions and the organic ligands as raw materials of MOF is contained in the first raw material solution and the other is contained in the second raw material solution.

[0115] In step S01 , preferably, as described above, the first raw material solution contains metal ions, and the second raw material solution contains organic ligands.

[0116] In addition to this structure, a structure in which the first raw material solution contains an organic ligand and the second raw material solution contains a metal ion may be adopted.

[0117] In the method for producing a composite sheet of the present embodiment, in step S01 , it is preferred that one of the first raw material solution and the second raw material solution contain water as a solvent and the other contain an organic solvent as a solvent.

[0118] In step S01 , as described above, it is preferred that the solvent of the first raw material solution contains water, and the solvent of the second raw material solution contains an organic solvent.

[0119] Besides this structure, a structure in which the solvent of the first raw material solution contains an organic solvent and the solvent of the second raw material solution contains water may be adopted.

[0120] In step S01 , a solvent other than ethanol may be used as the organic solvent, and for example, methanol, isopropanol, acetone, etc. may be included.

[0121] The organic solvent is preferably mixed with water at an arbitrary ratio.

[0122] In the method for manufacturing a composite sheet of the present embodiment, preferably in step S01, the content of water in one of the first raw material solution and the second raw material solution containing water as a solvent is set to 30% by mass or more and 99% by mass or less. In addition, in the method for manufacturing a composite sheet of the present embodiment, preferably in step S01, the content of an organic solvent in one of the first raw material solution and the second raw material solution containing an organic solvent as a solvent is set to 30% by mass or more and 99% by mass or less. By setting these numerical ranges, the raw material solution easily penetrates into the sheet substrate, and the MOF is easily fixed uniformly in the thickness direction of the composite sheet.

[0123] The method for producing a composite sheet of the present embodiment may include additional steps in addition to the above-mentioned steps as needed. In addition, in the method for producing a composite sheet of the present embodiment, part of the above-mentioned steps may be changed or omitted as needed.

[0124] For example, the drying in step S04 can be performed by heating at a temperature higher than room temperature and lower than the heat treatment temperature in step S05 , thereby shortening the processing time.

[0125] Furthermore, for example, by providing a step of drying the sheet base material in the heat treatment of step S05 , step S04 before step S05 (the last step S04 when steps S02 to S04 are repeated) may be omitted.

[0126] In the manufacturing method of the composite sheet of the present embodiment, the fibers constituting the sheet substrate may include fibers other than the core-sheath fibers. In this case, it is preferred that the fibers other than the core-sheath fibers also include organic fibers. Thus, in the manufacturing method of the composite sheet of the present embodiment, the MOF can be more firmly fixed to the surface of the organic fiber by the hydrophobic interaction between the organic ligands of the MOF and the groups present on the surface of the organic fiber.

[0127] In addition, such hydrophobic interactions occur not only in hydrophobic organic fibers, but also in hydrophilic organic fibers. That is, even if an organic fiber is hydrophilic as a whole, if there is a hydrophobic part at the microscopic level, a constitutive interaction will occur. For example, in the case of cellulose fibers, which are hydrophilic organic fibers, the C-H group constituting the axial group of the glucopyranose ring is hydrophobic, so a hydrophobic interaction occurs.

[0128] Whether the fiber constituting the sheet substrate in the composite sheet is hydrophilic or hydrophobic is determined by the actual surface properties of the fiber, regardless of the original properties of the fiber. That is, the surface-treated fiber is determined according to the state after the surface treatment. For example, a hydrophobic fiber whose surface has been hydrophilized is a hydrophilic fiber, and a hydrophilic fiber whose surface has been hydrophobized is a hydrophobic fiber.

[0129] In order to evaluate whether the fibers constituting the sheet substrate in the composite sheet are hydrophilic or hydrophobic, deionized water is sprayed on the composite sheet, and the contact surface between each fiber and the deionized water is observed using a microscope or a digital microscope. If the contact angle between the fiber and the deionized water is less than 60°, the surface of the fiber is judged to be hydrophilic, and if the contact angle is greater than 60°, the surface of the fiber is judged to be hydrophobic.

[0130] In the case where the fibers constituting the sheet substrate include fibers other than core-sheath fibers, the mass of only the core-sheath fibers can be determined as follows. That is, for the fibers constituting the sheet substrate in the composite sheet, the structural formula is determined using time-of-flight secondary ion mass spectrometry (TOF-SIMS), infrared spectroscopy (IR), nuclear magnetic resonance (NMR), energy dispersive X-ray spectroscopy (EDX), etc., and the melting point is measured by DSC, thereby determining the type of fiber. Then, the mass of the core-sheath fibers contained in the composite sheet can be calculated based on the intensity ratio of the NMR spectrum obtained from the 100% aggregate of the core-sheath fibers and the spectrum obtained from the composite sheet.

[0131] In the manufacturing method of the composite sheet of the present embodiment, it is preferred to use a sheet substrate containing both hydrophilic fibers and hydrophobic fibers. That is, it is preferred that in the sheet substrate used in the present embodiment, in addition to the core-sheath fibers as hydrophobic fibers, at least hydrophilic fibers are included, and hydrophobic fibers other than the core-sheath fibers may also be included. Thus, in step S03, for the sheet substrate impregnated with one of water and organic solvent, the penetration rate of the other becomes faster, so MOF is not easy to exist unevenly in the sheet substrate.

[0132] The sheet substrate of the present embodiment preferably contains, as hydrophilic organic fibers, one or more selected from cellulose fibers, regenerated cellulose fibers, thermoplastic fibers whose surfaces are hydrophilized, and the like.

[0133] The regenerated cellulose fiber more preferably contains one or more selected from rayon, cuprammonium fiber, and the like.

[0134] Examples of methods for hydrophilizing the surface of thermoplastic fibers include coating with a hydrophilizing agent and plasma treatment.

[0135] The thermoplastic fiber preferably contains one or more selected from the group consisting of polyolefin resins, polyester resins, vinyl resins, acrylic resins, fluororesins, and polyamide resins.

[0136] The polyolefin resin preferably contains one or more selected from polyethylene, polypropylene and the like.

[0137] The polyester resin preferably contains one or more selected from polyethylene terephthalate and the like.

[0138] The vinyl resin preferably contains one or more selected from polyvinyl chloride, polystyrene and the like.

[0139] The acrylic resin preferably contains one or more selected from polyacrylic acid, polymethyl methacrylate, and the like.

[0140] The fluororesin preferably contains one or more selected from polyperfluoroethylene and the like.

[0141] In addition, the sheet base material of the present embodiment preferably contains one or more types selected from synthetic fibers and the like as hydrophobic organic fibers.

[0142] The synthetic fiber preferably includes one or more selected from polyolefin fibers, polyester fibers, fluorine fibers, polyamide fibers and the like.

[0143] In addition, in the present embodiment, part or all of the fibers constituting the sheet substrate may be inorganic fibers. The sheet substrate of the present embodiment preferably contains, as inorganic fibers, one or more selected from glass fibers, ceramic fibers, metal fibers, carbon fibers, and the like.

[0144] [Detailed structure of composite sheet]

[0145] (Surface coverage)

[0146] In the composite sheet of the present embodiment, in step S03, MOF can be carried throughout the entire three-dimensional structure of the sheet substrate composed of fibers. That is, in the composite sheet of the present embodiment, a large amount of MOF can be carried not only on the surface of the sheet substrate, but also in the central portion in the thickness direction. Specifically, in the composite sheet of the present embodiment, in the central portion in the thickness direction of the composite sheet, the surface coverage rate specified as the ratio of the area covered by MOF in the surface of the fiber is preferably 60% or more, more preferably 70% or more, further preferably 80% or more, and in reality less than 100%.

[0147] The surface coverage rate achieved by MOF in the fiber constituting the sheet substrate of the composite sheet can be obtained using SEM and EDX. Specifically, the composite sheet is cut and the MOF that is not carried is removed with a blower or the like. Then, a microstructure photograph is taken by SEM for the entirety of its cut surface. In the obtained microstructure photograph, a vertical line is made relative to the straight line along the width direction of the composite sheet, and the midpoint between the two ends in the thickness direction of the composite sheet is determined on the vertical line. The portion on the straight line along the width direction passing through the midpoint is defined as the central part of the thickness direction of the composite sheet. Then, focusing on any one fiber existing in the central part of the thickness direction of the composite sheet, a microstructure photograph is taken by SEM for this one fiber, and an element mapping image is generated by EDX. Thus, the area where the fiber exists can be determined by a microstructure photograph, and the area where the metal exists can be defined as the area where MOF exists by an element mapping image. Moreover, the surface coverage rate can be calculated in the form of the ratio of the area where MOF exists in the entire area where the fiber exists.

[0148] (Circumferential coverage)

[0149] In the composite sheet of the present embodiment, MOF can be uniformly carried over the entire circumference of the surface of the fiber constituting the sheet substrate. Thus, in the composite sheet of the present embodiment, the circumferential coverage can be improved, which is defined as the ratio of the area covered by MOF in the surface of the fiber observed as the outline of the fiber in the cross section orthogonal to the length direction of the fiber constituting the sheet substrate. Specifically, in the composite sheet of the present embodiment, the circumferential coverage achieved by MOF in at least a portion of the fiber constituting the sheet substrate is preferably 80% or more, more preferably 85% or more, further preferably 90% or more, and less than 100% in reality. It is further preferred that the circumferential coverage achieved by MOF in at least a portion of the fiber constituting the middle region when the cross section of the composite sheet is equally divided into three regions in the thickness direction is 80% or more. In addition, the shape of the outline of the fiber is not particularly limited, and can be any shape such as a circle, a quadrilateral, a triangle, a star, etc. In any case, the length of the entire circumference of the surface of the fiber can be obtained by a known method, thereby calculating the circumferential coverage.

[0150] The circumferential coverage achieved by MOF in the surface of the fiber constituting the sheet substrate of the composite sheet can be obtained using SEM and EDX. Specifically, for the field of view of the cross section orthogonal to the length direction of the fiber in the cross section of the composite sheet, a microstructure photograph is taken by SEM, and an element mapping image is generated by EDX. Then, the length of the entire area of ​​the surface of the fiber observed as the outline of the fiber in the cross section orthogonal to the length direction of the fiber and the length of the area covered by MOF in the surface of the fiber observed as the outline of the fiber are measured, and the circumferential coverage can be calculated by the following formula in the form of their ratio.

[0151] Circumferential coverage by MOF (%) = 100 × (length of the area covered by MOF on the fiber surface / length of the entire area on the fiber surface)

[0152] (Thickness of the MOF layer covering the fiber)

[0153] Whether MOF covers the surface of the fiber and the thickness of the MOF layer covered are measured as follows. A two-liquid curable liquid epoxy resin is mixed with a curing agent and impregnated into the sheet of the measured object. Then, after degassing by vacuumization, a heat treatment is performed to cure the epoxy resin and the curing agent. Thus, a cured sample with the position of the fiber and MOF fixed is obtained.

[0154] The obtained cured sample was cut along the thickness direction of the sheet and its surface was observed by SEM. From the cross-sectional image of the obtained composite sheet, the cross-sectional portion of the fiber covered by MOF was extracted. The average value of the thickness of the MOF layer in the fiber radius direction of the portion covering the fiber was taken as the thickness of the MOF layer.

[0155] (MOF content ratio)

[0156] In the composite sheet of the present embodiment, as described above, by increasing the surface coverage and circumferential coverage of MOF in the fibers constituting the sheet substrate, more MOF can be carried on the sheet substrate, that is, the content of MOF can be increased. Specifically, in the composite sheet of the present embodiment, the content ratio of MOF, which is defined as the ratio of the mass of MOF to the mass of the entire composite sheet, is preferably 80% by mass or more, more preferably 85% by mass or more. In addition, in the composite sheet of the present embodiment, the content ratio of MOF is preferably 99% by mass or less.

[0157] The content ratio of MOF in the composite sheet can be obtained by analyzing the composite sheet. Specifically, gas adsorption measurement, X-ray diffraction (XRD), EDX, NMR, IR, elemental analysis, etc. are first performed to obtain the pore structure, lattice size, crystal structure, and constituent elements. By referring to these results and the public MOF database, the type of MOF, that is, the metal ions and organic ligands, is determined. Then, the composite sheet is thermally decomposed and the amount of metal contained in the remaining ash is measured. Next, the mass of MOF contained in the composite sheet is obtained from the measured amount of metal and the determined metal content of MOF. Then, the mass of MOF obtained is divided by the mass of the composite sheet to obtain the content ratio of MOF.

[0158] (MOF surface exposure rate)

[0159] In the composite sheet of the present embodiment, it is not necessary to mainly rely on an adhesive as a bonding component. Therefore, in the composite sheet of the present embodiment, the adhesive does not cover the surface of the MOF, and the surface exposure rate can be increased. The surface exposure rate is defined as the ratio of the area of ​​the region where the surface of the MOF is exposed to the area occupied by the MOF carried on the sheath portion of the core-sheath fiber constituting the sheet substrate when the composite sheet is viewed from above (100×(area of ​​the region where the surface of the MOF is exposed) / (area of ​​the region occupied by the MOF carried on the sheath portion of the core-sheath fiber constituting the sheet substrate)). Specifically, in the composite sheet of the present embodiment, the surface exposure rate of the MOF is preferably greater than 50% and less than 100%, more preferably greater than 70%, and even more preferably greater than 90%.

[0160] The measurement of the surface exposure rate of MOF in the composite sheet is first performed by removing the MOF that is not carried on the sheath part of the core-sheath fiber constituting the sheet substrate in the composite sheet by a blower or the like. Next, the surface of the MOF carried on the sheath part of the core-sheath fiber constituting the sheet substrate is analyzed and mapped by using TOF-SIMS, micro-IR, etc., and an evaluation can be performed. Specifically, the part where the MOF can be observed is identified, and its area (the area of ​​the area occupied by the MOF) is measured and the MOF surface is analyzed. By analyzing the MOF surface, the area of ​​the region where the spectrum from substances other than MOF is detected on the MOF is measured. Substances other than MOF refer to substances from adhesives, etc. Then, the area of ​​the region where the spectrum from substances other than MOF is detected is subtracted from the area occupied by MOF. The surface exposure rate of MOF can be calculated by dividing the area of ​​the difference by the surface area of ​​MOF.

[0161] (Gas adsorption amount per unit volume of composite sheet)

[0162] Also in the composite sheet of the present embodiment, the surface of MOF is not covered by the adhesion of the adhesive. Therefore, the surface exposure rate of MOF is high. Moreover, in the composite sheet of the present embodiment, as described by comparison with the comparative structural example in the above-mentioned "Step S03: Impregnation with the Second Raw Material Solution", there are few unreacted MOFs. Therefore, it is not easy to hinder the gas adsorption performance. Therefore, in the composite sheet of the present embodiment, the MOF carried on the sheet substrate can effectively exert its original gas adsorption performance. In addition, the MOF can also be fixed on the fibers in the center of the composite sheet, and the air permeability is also high. Therefore, in the composite sheet of the present embodiment, the gas adsorption amount per unit volume of the composite sheet can be increased. Specifically, in the composite sheet of the present embodiment, for example, when using a MOF that selectively adsorbs carbon dioxide, the gas adsorption amount per unit volume of the composite sheet is preferably 2mL / cm 3 More preferably, 3 mL / cm 3 More preferably, 5 mL / cm 3 above.

[0163] The gas adsorption amount per unit volume of the composite sheet is obtained by dividing the gas adsorption amount measured for the composite sheet by the measured volume of the composite sheet. The gas adsorption amount is measured using a high-precision gas adsorption amount measuring device "BELSORP-miniII" manufactured by MicrotracBEL.

[0164] (MOF shedding rate)

[0165] In the composite sheet of this embodiment, the MOF can be firmly fixed to the fiber surface by the intermolecular force acting between the fiber surface and the MOF, without relying mainly on a binder as an adhesive component for fixing the MOF to the fiber surface.

[0166] In the composite sheet of this embodiment, MOF is melt-fixed by utilizing the sheath portion constituting the surface of the core-sheath fiber, so that a particularly high fixing strength of MOF can be obtained on the surface of the core-sheath fiber. Therefore, in the composite sheet of this embodiment, MOF is not easy to fall off from the sheet substrate.

[0167] In the composite sheet of the present embodiment, the MOF shedding rate obtained by evaluating the vibration of the composite sheet by holding it in the hand and vibrating it up and down is preferably greater than 0 mass % and less than 20 mass %, more preferably less than 18 mass %, further preferably less than 15 mass %, and further preferably less than 9 mass %.

[0168] Thus, in the composite sheet of this embodiment, it is easy to maintain the amount of MOF carried on the sheet substrate during transportation or use, so it is not easy to reduce the gas adsorption performance. In addition, in the composite sheet of this embodiment, it is possible to prevent the MOF that falls off during use from mixing into the equipment as foreign matter.

[0169] The MOF shedding rate was obtained by dividing the mass of MOF shedding during the shaking evaluation by the mass of MOF contained in the composite sheet before the shaking evaluation.

[0170] (Maximum bending stress of composite sheet)

[0171] In the composite sheet of this embodiment, high flexibility is easily obtained by adopting a structure that does not mainly rely on an adhesive as an adhesive component for fixing MOF on the surface of the fiber. Thus, the composite sheet of this embodiment can obtain high processability and can be stored and transported in a rolled form.

[0172] In the composite sheet of the present embodiment, the maximum bending stress is preferably 0 MPa or more and 5 MPa or less, more preferably 3 MPa or less, further preferably 1 MPa or less, and further preferably 0.1 MPa or less.

[0173] The maximum bending stress in the composite sheet can be measured using a measuring device (universal testing machine AG-X plus manufactured by Shimadzu Corporation) in accordance with the three-point bending test of JIS K7017. At this time, the composite sheet as a measurement sample is cut into a sample of 100 mm in length and 100 mm in width for measurement.

[0174] Three-point bending evaluation: The sample is placed in a fixture with a support distance of 40 mm, and the center between the support points is pressed at a speed of 10 mm / min to measure the amount of pressure and the bending load. Then, the maximum value of the bending stress obtained by this evaluation is taken as the maximum bending stress.

[0175] The bending stress is a physical property value calculated by dividing the moment (product of load and distance) applied to the sample during the three-point bending test by the section modulus of the sample, and is calculated by the following formula.

[0176] Bending stress (MPa) = 3 × bending load (N) × distance between supporting points (m) / 2 / sample thickness (m) / (sample width (m) 2 ) / 10 6

[0177] When the sample cannot be cut out in the size of the composite sheet to be measured, a sample having an arbitrary size may be cut out for measurement.

[0178] (Gurley air permeability of composite sheet)

[0179] In the composite sheet of the present embodiment, in order to easily supply gas to the MOF carried in the central part of the thickness direction of the composite sheet, it is preferably configured so that the gas can pass through with low pressure loss. Specifically, in the composite sheet of the present embodiment, the Gurley air permeability is preferably 0 seconds / 100mL or more and 10 seconds / 100mL or less, more preferably 5 seconds / 100mL or less, and further preferably 0.5 seconds / 100mL or less. The Gurley air permeability of the composite sheet can be obtained using a Gurley-type air permeability tester according to JIS P8117:2009.

[0180] In the composite sheet of the present embodiment, since the Gurley air permeability is high, it is possible to suppress a reduction in the amount of MOF supported due to fixation caused by contact between the sheath portions of the core-sheath fibers during the heat treatment in step S05 .

[0181] (Determination of the Type of Fiber Constituting Sheet Base Material)

[0182] The type of fiber constituting the sheet substrate in the composite sheet can be determined using TOF-SIMS, IR, NMR, EDX, differential scanning calorimetry (DSC), etc. Specifically, for the fiber constituting the sheet substrate in the composite sheet, the structural formula is determined using TOF-SIMS, IR, NMR, EDX, etc., and the melting point is measured by DSC, thereby determining the type of fiber.

[0183] [Other embodiments]

[0184] As mentioned above, although embodiment of the present invention was described, the present invention is not limited to the above-mentioned embodiment, and various changes can be added without departing from the scope of the gist of the present invention.

[0185] For example, in the method for manufacturing a composite sheet of the present embodiment, from the perspective of the penetration rate of the first raw material solution and the second raw material solution into the sheet substrate, as the solvent used in the first raw material solution and the second raw material solution prepared in step S01, it is preferred that one contains water and the other contains an organic solvent, but from other perspectives, a structure different from it may also be adopted. For example, in the method for manufacturing a composite sheet of the present embodiment, any one of the solvents used in the first raw material solution and the second raw material solution prepared in step S01 may contain water or an organic solvent.

[0186] The composite sheet of the present embodiment preferably does not contain an adhesive, but may contain a small amount of an adhesive when it is necessary to more firmly fix the MOF to the sheet substrate, etc. However, in the composite sheet of the present embodiment, from the viewpoint of ensuring high gas adsorption performance of MOF, ensuring high flexibility, etc., the ratio of the mass of the adhesive to the total mass of the MOF and the adhesive is preferably limited to 0 mass % or more and 5 mass % or less.

[0187] In the composite sheet of the present embodiment, the content of the binder relative to the mass of the entire composite sheet is 0 mass % to 10 mass %, preferably 5 mass % or less, and more preferably 1 mass % or less.

[0188] [Examples and Comparative Examples]

[0189] (Examples 1 and 2)

[0190] As an example of the present invention, a sample of a composite sheet was produced using the above-mentioned production method.

[0191] As the sheet substrate, an air-laid nonwoven fabric (weight 40 g / m2) containing hydrophilic fibers and hydrophobic fibers at the mass ratio shown in Table 1 was used. 2 ). In Examples 1 and 2, coniferous chemical pulp (NBKP) as a cellulose fiber was used as the hydrophilic organic fiber. In addition, as the hydrophobic organic fiber, a core-sheath fiber was used, in which the core portion was composed of polyethylene terephthalate (PET) with a melting point of 260°C and the sheath portion was composed of polyethylene (PE) with a melting point of 130°C. The content of the core-sheath fiber in the sheet base material was 70% by mass.

[0192] As MOF, ELM-11 which is configured to selectively adsorb carbon dioxide was used.

[0193] Table 1 shows the thickness of the composite sheet, the number of times steps S02 to S04 were performed, and the heat treatment temperature in step S05.

[0194] The specific structures of steps S01 to S05 are as follows.

[0195] As step S01, a Cu(BF4)2 aqueous solution is diluted with deionized water to 0.125 mol / L to prepare a first raw material solution. Also, bpy is dissolved with ethanol to 1 mol / L to prepare a second raw material solution.

[0196] In step S02, 14 g of the first raw material solution was applied to a sheet substrate of 100×100 mm using a dropper.

[0197] In step S03, 2.4 g of the second raw material solution was applied with a dropper to the sheet substrate coated with the first raw material solution in step S02 before the sheet substrate dried.

[0198] As step S04, the sheet substrate coated with the second raw material solution in step S03 is dried overnight in a fume hood.

[0199] Steps S02 to S04 are repeated the number of times listed in Table 1.

[0200] As step S05, the sheet on which steps S02 to S04 were repeated the number of times described in Table 1 was left to stand in a drying oven at the heat treatment temperature described in Table 1 for 2 hours.

[0201] For the composite sheet sample, the above-mentioned analysis method was used to determine the MOF content ratio, circumferential coverage, surface exposure rate, and gas adsorption per unit volume. The circumferential coverage was determined in the fibers constituting the central portion of the composite sheet in the thickness direction. More specifically, the MOF content ratio and gas adsorption per unit volume were determined as follows.

[0202] ·MOF content ratio

[0203] The mass of the obtained composite sheet and the mass of the substrate sheet alone before the MOF was supported were calculated by the following formula.

[0204] Content ratio of MOF (%) = 100 × (mass of composite sheet - mass of substrate sheet alone) / mass of sample

[0205] Gas adsorption per unit volume

[0206] The composite sheet sample was cut into any size. BELSORP-miniII (manufactured by Microtrac BEL) was used for the evaluation of the gas adsorption amount. As a pretreatment, a vacuum degassing treatment was performed at 100°C for 12 hours, and then the adsorption isotherm of carbon dioxide was measured. The adsorption amount obtained from this result was taken as the adsorption amount of carbon dioxide, and divided by the volume of the composite sheet sample measured, thereby calculating the gas adsorption amount per unit volume.

[0207] The analysis results of the composite sheet samples are shown in Table 2. As shown in Table 2, the circumferential coverage of the composite sheet samples of Examples 1 and 2 was 100%. As a result, a high MOF content of 80% by mass or more was obtained in both samples.

[0208] In addition, the surface exposure rate of MOF was 100% in all cases, and the gas adsorption amount of MOF per unit volume was also high. Therefore, it is presumed that the support of MOF by the sheet substrate suppressed the decrease in gas adsorption performance of MOF.

[0209] In addition, the fibers all maintained their morphology. In the core-sheath fiber, it was confirmed that MOF was melted and fixed to the resin of the sheath portion, thereby fixing MOF to the sheath portion. In addition, a MOF layer was formed on the surface of the fiber.

[0210] Next, the MOF shedding rate, maximum bending stress, MOF uniformity, processability, and Gurley air permeability were evaluated for each sample. Regarding processability, filling evaluation and MOF retention evaluation were performed. In more detail, the uniformity and processability of MOF were evaluated as follows.

[0211] ·MOF uniformity

[0212] The sample of the composite sheet is cut along the thickness direction to make the observation surface of the cross section. Then, a microstructure photograph obtained by SEM and an element mapping image obtained by EDX are generated. At this time, each area after the thickness direction of the sample of the composite sheet is divided into three parts is in the observation and analysis area. From the obtained element mapping image, the content of the metal as the main component of MOF is quantified, and the average value of the content of the metal as the main component of MOF in the area after being divided into three parts and the evaluation value of its uniformity are calculated by the following formula.

[0213] Evaluation value of uniformity (%) = 100 × (maximum value of the content of the metal as the main component of MOF - minimum value of the content of the metal as the main component of MOF) / average value of the content of the metal as the main component of MOF in the area divided into three parts

[0214] The numerical value obtained by rounding off the evaluation value of uniformity obtained above is taken as the evaluation result of uniformity of MOF. That is, in each composite sheet sample, the smaller the numerical value of the evaluation result, the higher the uniformity of MOF, and the larger the numerical value of the evaluation result, the lower the uniformity of MOF.

[0215] Processability

[0216] As evaluations of processability, evaluations of filling properties and MOF retention properties were performed.

[0217] (1) Filling evaluation

[0218] The composite sheet was cut into pieces with a width of 5 cm and a length of 10 cm, and the cut sample was wound around a cylinder with a diameter of 1.5 mm along the outer circumference.

[0219] The stacking state of the obtained winding body is confirmed, and the state of the gap between the stacked composite sheet samples is confirmed. For each composite sheet sample, the maximum value of the gap is used as the evaluation result of the filling property. In other words, in each composite sheet sample, the smaller the value of the evaluation result is, the higher the filling property of the winding body can be obtained.

[0220] (2) Evaluation of MOF retention

[0221] The mass of the composite sheet was measured before and after the filling property evaluation test, and the retention rate of MOF was calculated by the following formula.

[0222] MOF retention rate (%) = 100 × (mass of composite sheet after filling evaluation test / mass of composite sheet before filling evaluation test)

[0223] The MOF retention rate was used as the evaluation result of the MOF retention evaluation. That is, it was found that, in each composite sheet sample, the larger the evaluation result value, the better the state of MOF supported on the fiber surface could be maintained when processed into a wound body.

[0224] As shown in Table 2, the shedding rate of MOF is very small, less than 10% by mass, and the maximum bending stress is also very small, 0.03MPa. As a result, regarding processability, the gaps in the filling evaluation are limited to less than 2mm, and in the MOF retention evaluation, they are all above 97%, and good evaluation results are obtained. In addition, the values ​​of the uniformity of MOF are all limited to less than 20%, and it can be seen that MOF is dispersed with high uniformity throughout the entire sheet substrate. Moreover, the Gurley air permeability is very small, 0.1 seconds / 100mL, and high air permeability is obtained. It is believed that the high air permeability in each sample helps to increase the gas adsorption amount per unit volume.

[0225] In any of the examples, the gas adsorption per unit volume is greater than that in the following comparative example 1. This is believed to be because the MOF is not covered by the resin and can exert its original gas adsorption function. In addition, in any of the examples, the maximum bending stress is smaller than that in the following comparative example 1, the gap is smaller in the filling evaluation, and the Gurley air permeability is larger. This is believed to be due to the fact that there is no adverse effect caused by the melting of the resin.

[0226] It is known that in any embodiment, the uniformity of MOF is smaller than that of the following Comparative Example 2, and the dispersibility of MOF is higher. It is believed that this is because MOF particles are formed on the sheet substrate, and MOF is uniformly arranged on the entire sheet substrate. As a result, it is believed that in any embodiment, the circumferential coverage of the central part of the composite sheet in the thickness direction is higher than that of Comparative Example 2.

[0227] In any of the examples, the gas adsorption amount per unit volume was larger than that of Comparative Example 3 described below. This is considered to be because the MOF supported on the surface of the fiber was not coated with the resin and was able to exert its original gas adsorption function.

[0228] In addition, in all Examples, the maximum bending stress was smaller than that in Comparative Example 3, and the gap in the filling property evaluation regarding processability was smaller. This is considered to be because there was no adverse effect due to melting of the resin.

[0229] Furthermore, it is found that in all examples, the values ​​of MOF uniformity are smaller and the dispersibility of MOF is higher than that in Comparative Example 3. This is considered to be because MOF particles are formed on the sheet substrate, so that MOF is uniformly arranged on the entire sheet substrate.

[0230] In all examples, the gas adsorption amount per unit volume was significantly increased compared to Comparative Example 4. This is considered to be because the MOF was not covered with the resin and was able to exert its original gas adsorption function.

[0231] In addition, it can be seen that in any embodiment, the uniformity of MOF is smaller than that in Comparative Example 4, and the dispersibility of MOF is higher. It is believed that this is because MOF particles are formed on the sheet substrate, and MOF is uniformly arranged on the entire sheet substrate. As a result, it is believed that in any embodiment, the circumferential coverage in the central part of the thickness direction of the composite sheet is higher than that in Comparative Example 4.

[0232] (Comparative Examples 1 to 4)

[0233] Samples of the composite sheets of the comparative examples were prepared under the conditions shown in Table 1. The same analysis and evaluation as in Examples 1 and 2 were performed on each sample. The analysis results and evaluation results of each sample are shown in Table 2. Comparative Examples 1 to 4 are described in detail below.

[0234] Comparative Example 1

[0235] In Comparative Example 1, a hot air nonwoven fabric (weight 40 g / m 2 ) The content of the core-sheath fibers in the sheet base material was 0% by mass.

[0236] Instead of steps S02 to S04 of the above embodiment, pre-generated MOF particles (average particle size 5 μm) were spread on both sides of the sheet substrate at the MOF content ratio shown in Table 2, and after pressurization at room temperature, heat treatment was performed at 140° C. for 2 hours. In the obtained composite sheet, the PE fibers composed only of PE with a low melting point melted due to the heat treatment and could not maintain the form of fibers, and the molten resin partially covered the MOF.

[0237] Comparative Example 2

[0238] In Comparative Example 2, the same nonwoven fabric as in Example 1 was used as the sheet base material.

[0239] Instead of steps S02 to S04 of the above embodiment, preliminarily produced MOF particles (average particle size 5 μm) were dispersed at the MOF content ratio shown in Table 2, and after pressurization at room temperature, heat treatment was performed at 140° C. for 2 hours.

[0240] In Comparative Example 2, the fibers in the composite sheet maintained their morphology.

[0241] Comparative Example 3

[0242] In Comparative Example 3, the same nonwoven fabric as in Example 1 was used as the sheet base material.

[0243] Instead of steps S02 to S04 of the above embodiment, a pre-produced MOF dispersion was spread on both sides of the sheet substrate, followed by a heat treatment at 140° C. for 2 hours. The composition of the MOF dispersion used in Comparative Example 3 is as follows.

[0244] Average particle size of MOF: 5 μm

[0245] Adhesive: Water-soluble PVA

[0246] MOF / binder ratio: 1 / 1

[0247] Solvent: Deionized water

[0248] Solid content / 20%

[0249] In the composite sheet sample of Comparative Example 3, MOF was not directly supported on the fiber surface. In all composite sheet samples, the surface of MOF was partially covered due to melting of the sheath portion of the core-sheath fiber or contact with the binder.

[0250] Comparative Example 4

[0251] In Comparative Example 4, the same nonwoven fabric as in Example 1 was used as the sheet base material.

[0252] Instead of steps S02 to S04 of the above embodiment, preliminarily produced MOF particles (average particle size: 5 μm) were spread on both surfaces of the sheet substrate at the MOF content ratio shown in Table 2.

[0253] Comparative Example 4 did not perform heat treatment, so the MOF particles were not fixed by melting the sheath portion of the core-sheath fiber. In the measurement of the gas adsorption amount per unit volume in the obtained composite sheet, a large amount of MOF fell off during the processing and preparation of the sample.

[0254] [Table 1]

[0255]

[0256] [Table 2]

[0257]

Claims

1. A composite sheet comprising a sheet substrate composed of fibers and a metal organic structure dispersed therein, wherein: The fiber includes a core-sheath fiber having a core-sheath structure consisting of a core part and a sheath part, The metal organic structure is supported by the resin of the sheath portion of the core sheath fiber being melted and fixed. The surface exposure rate of the metal organic structure carried by the sheath portion of the core-sheath fiber is 50% or more.

2. The composite sheet according to claim 1, characterized in that: In at least a portion of the fiber, a circumferential coverage rate of the metal-organic structure in a cross section perpendicular to the longitudinal direction is 80% or more and 100% or less, preferably 85% or more, and more preferably 90% or more.

3. The composite sheet according to claim 1 or 2, characterized in that: The core portion of the core-sheath fiber includes a resin component having a melting point of 160° C. or higher and 280° C. or lower, preferably 200° C. or higher, and more preferably 240° C. or higher.

4. The composite sheet according to any one of claims 1 to 3, characterized in that: The sheath portion of the core-sheath fiber includes a resin component having a melting point of 70° C. or higher and lower than 160° C., preferably 80° C. or higher, and more preferably 100° C. or higher.

5. The composite sheet according to any one of claims 1 to 4, characterized in that: In the core-sheath fiber, the core portion contains a resin with a higher melting point than the resin contained in the sheath portion, and the difference between the melting point of the resin component contained in the core portion and the melting point of the resin component contained in the sheath portion is preferably above 10°C and below 200°C, more preferably above 60°C, and further preferably above 100°C.

6. The composite sheet according to any one of claims 1 to 5, characterized in that: The melting point of the resin component of the core portion of the core-sheath fiber is higher than the melting point of the resin component of the sheath portion by 10° C. or more.

7. The composite sheet according to any one of claims 1 to 6, characterized in that: The shedding rate of the metal organic structure obtained by shaking evaluation was 20 mass % or less.

8. The composite sheet according to any one of claims 1 to 7, characterized in that: The shedding rate of the metal organic structure obtained by the shaking evaluation is 0 mass % or more and 20 mass % or less, preferably 18 mass % or less.

9. The composite sheet according to any one of claims 1 to 8, characterized in that: The maximum bending stress is below 5 MPa.

10. The composite sheet according to any one of claims 1 to 9, characterized in that: The maximum bending stress is 0 MPa or more and 5 MPa or less, preferably 3 MPa or less, and more preferably 1 MPa or less.

11. The composite sheet according to any one of claims 1 to 10, characterized in that: The thickness of the composite sheet is 0.2 mm to 10 mm, preferably 0.5 mm to 5 mm, and more preferably 1 mm or more.

12. The composite sheet according to any one of claims 1 to 11, characterized in that: The Gurley air permeability of the composite sheet is 0 sec / 100 mL or more and 10 sec / 100 mL or less, preferably 5 sec / 100 mL or less, and more preferably 0.5 sec / 100 mL or less.

13. The composite sheet according to any one of claims 1 to 12, characterized in that: The content ratio of the metal organic structure is 80 mass % or more and 99 mass % or less, preferably 85 mass % or more, based on the mass of the entire composite sheet.

14. The composite sheet according to any one of claims 1 to 13, characterized in that: The surface coverage of the fibers constituting the center portion in the thickness direction of the composite sheet by the metal organic structure is 60% or more and 100% or less, preferably 70% or more, and more preferably 80% or more.

15. The composite sheet according to any one of claims 1 to 14, characterized in that: The surface exposure rate of the metal organic structure is 50% or more and 100% or less, preferably 70% or more, and more preferably 90% or more.

16. The composite sheet according to any one of claims 1 to 15, characterized in that: The metal organic structure layer is formed on the surface of the fiber.

17. The composite sheet according to claim 16, wherein: The metal-organic structure layer is a film in which the metal-organic structure integrally covers the surface of the fiber.

18. The composite sheet according to any one of claims 1 to 17, characterized in that: The metal organic structure is configured to selectively adsorb carbon dioxide.

19. The composite sheet according to any one of claims 1 to 18, characterized in that: The composite sheet does not contain a binder.

20. The composite sheet according to any one of claims 1 to 19, characterized in that: The sheet substrate is nonwoven fabric.

21. The composite sheet according to any one of claims 1 to 20, characterized in that: The fiber maintains the form as a fiber in the core portion.

22. A method for producing a composite sheet, wherein a metal organic structure is supported on a sheet substrate composed of fibers including core-sheath fibers, the method for producing a composite sheet comprising: preparing a first raw material solution containing one of a metal ion and an organic ligand as raw materials of the metal organic structure and a second raw material solution containing the other, impregnating the sheet substrate with the first raw material solution, The second raw material solution is impregnated into the sheet substrate while the first raw material solution impregnated into the sheet substrate is not dried. The sheet base material impregnated with the second raw material solution is subjected to heat treatment.

23. The method for manufacturing a composite sheet according to claim 22, wherein: One of the first raw material solution and the second raw material solution contains 30% by mass or more and 99% by mass or less of water, and the other contains 30% by mass or more and 99% by mass or less of an organic solvent.

24. The method for manufacturing a composite sheet according to claim 22 or 23, characterized in that: The first raw material solution contains the metal ions, and the second raw material solution contains the organic ligand.

25. The method for manufacturing a composite sheet according to claim 24, wherein: The solvent of the first raw material solution includes water, and the solvent of the second raw material solution includes an organic solvent.

26. The method for producing a composite sheet according to any one of claims 22 to 25, characterized in that: Prior to the heat treatment, the sheet base material impregnated with the second raw material solution is dried.

27. The method for manufacturing a composite sheet according to claim 26, wherein: Prior to the heat treatment, the following steps are performed a total of 1 or more times and 20 or less times, preferably 2 or more times, and more preferably 3 or more times: impregnating the sheet substrate with the first raw material solution, The second raw material solution is impregnated into the sheet substrate while the first raw material solution impregnated into the sheet substrate is not dried. The sheet base material impregnated with the second raw material solution is dried.

28. The method for producing a composite sheet according to any one of claims 22 to 27, wherein: The metal organic structure is dehydrated by the heat treatment.

29. The method for producing a composite sheet according to any one of claims 22 to 28, wherein: In the core-sheath fiber, the melting point of the resin component contained in the core portion is higher than the temperature of the heat treatment, and the melting point of the resin component contained in the sheath portion is higher than the drying temperature and lower than the temperature of the heat treatment.

30. A composite sheet, characterized in that: The present invention is produced by the production method according to any one of claims 22 to 29.

Citation Information

Patent Citations

  • Composite of cellulose and metal organic framework, and production method for the same

    JP2021191913A

  • Fibers with absorbent particles adhered thereto, methods for their production and articles thereof

    US20210189620A1